PENYULUHAN TENTANG SENAM LANSIA KEPADA LANSIA DI WILAYAH KERJA PUSKESMAS DI DESA LABUHAN RASOKI TAHUN 2020PENYULUHAN TENTANG SENAM LANSIA KEPADA LANSIA DI WILAYAH KERJA PUSKESMAS DI DESA LABUHAN RASOKI TAHUN 2020 - Rangkuti, Nur Aliyah; Ramadhini, Delfi (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
Elderly exercise is a mild exercise and is easy to do, a burdensome action that is applied to the elderly. This exercise activity will help the body to stay in shape and stay fresh because it keeps the bones strong, encourages the heart to work optimally and helps eliminate free radicals that roam the body. Types of sports that can be done in the elderly include elderly exercise. This sport activity will help the body stay fit and fresh because it keeps the bones strong, encourages the heart to work optimally, and helps eliminate free radicals that roam in the body. The purpose of this service is to increase public knowledge about elderly gymnastics in the Rasoki harbor clinic. This activity is in the form of delivering information about the ways and steps of elderly gymnastics. The number of participants in the activities totaled 32 people. The elderly seemed enthusiastic in participating in the activities and giving feedback. The elderly are expected to have awareness to maintain health, especially to prevent the occurrence of diseases that are often experienced by the elderly whose ultimate goal is to increase the degree of optimal health.